2021
DOI: 10.21744/lingcure.v5ns1.1466
|View full text |Cite
|
Sign up to set email alerts
|

Social media promotion effect on product purchase decisions through word of mouth marketing

Abstract: This study aims to describe: (1). Promotion uses social media to influence purchasing decisions (2). Promotion with social media so that it can influence the word of mouth market (3) Promotion of word of mouth market in influencing product purchases (4) Promotion using social media word of mouth market in influencing product purchases. The method uses Quantitave, data collection techniques with questionnaires, samples with purposive sampling with a total of 150. Conclusions: (1) Social media promotion has an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This cannot be separated from using the right promotional media so that it has a good impact and is right on target. The presence of various social media supported by the power of the internet can make it easier to do promotions (Wursan et al, 2021). Promotion through online media can be done using Facebook, Instagram, WhatsApp, YouTube, Twitter, blogs, etc.…”
Section: Sub Discussionmentioning
confidence: 99%
“…This cannot be separated from using the right promotional media so that it has a good impact and is right on target. The presence of various social media supported by the power of the internet can make it easier to do promotions (Wursan et al, 2021). Promotion through online media can be done using Facebook, Instagram, WhatsApp, YouTube, Twitter, blogs, etc.…”
Section: Sub Discussionmentioning
confidence: 99%
“…Due to the pandemic, social media was the best tool they could use to interact with their clients, and the power of word-of-mouth also played a role with the same aims. According to Wursan et al (2021), the decision to purchase a green product is positively influenced by word-ofmouth, which also has a significant impact on business performance. Due to the pandemic, the finding showed that there have been adjustments made to price strategy, production planning, promotion, and packaging that realign the value delivered to customers (Toha et al, 2020).…”
Section: The Implementation Of Eco-marketing Innovation Within the Or...mentioning
confidence: 99%
“…Social media can promote an item quickly. People are more likely to buy an item when they are frequently immersed in the environment rendered by social media [9,10]. Social media affects people's daily lives.…”
Section: The Impact Of Social Media On People's Livesmentioning
confidence: 99%